1999
DOI: 10.1074/jbc.274.13.9013
|View full text |Cite
|
Sign up to set email alerts
|

CREB-binding Protein Is a Transcriptional Coactivator for Hepatocyte Nuclear Factor-4 and Enhances Apolipoprotein Gene Expression

Abstract: Hepatocyte nuclear factor-4 (HNF-4) is a liver-enriched transcription factor that is crucial in the regula

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
11

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 61 publications
3
70
0
11
Order By: Relevance
“…p160 proteins typically link other coactivators to the transcription initiation complex, whereas CBP/p300 can directly acetylate histones and/or other components of the transcription initiation complex (47). Similarly, orphan receptor HNF-4a was shown to interact with CBP/ p300 and GRIP-1 (48,49). In line with these studies, we found that CBP and GRIP-1 were associated with HNF-4a at the proximal vegf-D promoter (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…p160 proteins typically link other coactivators to the transcription initiation complex, whereas CBP/p300 can directly acetylate histones and/or other components of the transcription initiation complex (47). Similarly, orphan receptor HNF-4a was shown to interact with CBP/ p300 and GRIP-1 (48,49). In line with these studies, we found that CBP and GRIP-1 were associated with HNF-4a at the proximal vegf-D promoter (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…In analogy with other nuclear receptors, transactivation of HNF-4␣ is mediated by protein coactivators (e.g. CBP (cAMP-response element-binding protein (CREB)-binding protein)/P300, PGC-1, and others) (27)(28)(29)(30).…”
Section: Hnf-4␣mentioning
confidence: 99%
“…The co-activator peroxisome proliferative activated receptor, gamma, coactivator 1 alpha (PPARGC1A) also activates Pck1 expression through specific interaction with HNF4A, without binding directly to the Pck1 promoter [25]. HNF4A has been associated with recruiting coactivator protein (CREB binding protein/ p300) and the ability to mediate chromatin remodelling [26][27][28]. Whether these other regulators are also involved in stimulating PCK gene transcription directly in response to early glucocorticoid exposure was not explored in the report by Nyirenda et al [17].…”
mentioning
confidence: 99%